Evolution of viral populations in individuals infected with single and multiple HIV subtypes : a study of HIV-1 dual infection in a high risk cohort of female bar workers from Tanzania - Malaza, Abraham Lucky (Institute of Infectious Disease and Molecular Medicine, 2024)
The Human Immunodeficiency virus (HIV) is characterized by high replication rate and high levels of diversity resulting in numerous quasispecies that form a 'swarm' in the infected individual. HIV diversification is driven by selection pressure exerted by the host. The role of high viral diversity in disease progression in context of infection with more than one subtype (dual infection) is not elucidated. Delineating of the evolving viral diversity in dual infection will contribute to our understMding of HIV pathogenesis and thus enable for better strategies for effective therapy and vaccine development strategies. This study forms part of the HIV Superinfection Study (HISIS, www.mmrp.org) which aimed to identify the frequency of dual and superinfection in a high risk cohort of women in Mbeya, Tanzania. The Mbeya region is characterized by a highly diverse HIV epidemic where multiple HIV-1 subtypes co-circulate including A, C, and D, as well as recombinant forms. The aims of this thesis were: firstly, to investigate the distribution of HIV subtypes and recombinant forms in a cohort from Mbeya, and to determine the prevalence of HIV dual infection using the multi region hybridization assay (MHA); secondly to investigate the dynamics of viral evolution among dually infected individuals using a gel based screening assay (heteroduplex mobility assay, HMA) and sequencing, lastly the study aimed to investigate the role of point mutations and recombination on viral diversity and immune escape in a dually infected individual. The MHA was used to screen for different subtypes present in the study population (n=57). Subtypes A, C, D and their recombinants forms were detected. Subtype A accounted for 5%, C 33%, D 7% and recombinants 44%. Dual infection was detected in 11 % of individuals. AC recombinants accounted for 60% of all recombinant viral strains, ACD and CD strains accounted for approximately 12% each and AD recombinants accounted for 16%. This study provides additional information on the virus strains circulating in Tanzania. Overall these studies confirm that Tanzania harbours a complex diversity of viruses with a large proportion of the viruses being recombinant forms. The high prevalence of dual infections is clearly fuelling the generation of these recombinant viruses and it would be of interest to monitor the molecular epidemiology of the epidemic to determine if new circulating recombinant forms emerge. In a selected subset of chronically infected participants monitored over 21 months, we identified dual infection in four out of the twelve individuals. The presence of dual infections was screened for using the HMA based on the vpu and env C2C3 regions of the genome. Sequencing was employed to cpnfirm subtypes. Abstract 111 Four of the twelve women were dually infected with two distinct subtypes (A and C). The majority of single infections were by subtype C (n= 4), two were infected with subtype A, while subtype D was responsible for one infection. One individual was infected by a CD recombinant virus. Analysis of 20 randomly selected clones from different timepoints was used to determine diversity at selected timepoints. Env C2C3 region was more diverse than the vpu region with the mean DNA distances of vpu ranging from 0.9% to 8.5% compared to 0.3% and 19.5% in the env C2C3 region. Tz14 was found to harbour the most diverse viral strains with a maximum DNA distance of 12% (median 7%) in the vpu region and 14% (median 11 %) in the env C2C3 region. This individual was selected for an indepth analysis of the role of point mutations and recombination on viral evolution in dual infection. Analysis of clones from different timepoints demonstrated that dual infections were detectable in a minority of follow-up visits with only one individual having detectable dual infection at most timepoints. This emphasizes the importance of analyzing multiple time-points and that cross-sectional studies will likely underestimate the prevalence of dual infections. An analysis of the contribution of different viral variants in dual infection to overall viral burden illustrated large fluctuations of viral populations over time. However, generally the viral populations were relatively homogeneous at single time point suggesting that, while there is very high potential diversity, this diversity is largely constrained. Lastly, through full-length gene (gag and nef) sequencing we investigated positive selection, recombination patterns and screened for evidence of CTL escape in a dually infected individual (Tz14) over time (21 months). No evidence of positive selection was detected in both genes during the study period. Recombination analysis revealed that gag sequences had similar break points at time point F0 and F7. Furthermore, it was shown that none of the sequences obtained from both genes were 'pure' subtypes. Limited evidence of predicted CTL escape was observed in the nef and gag. Based on these results we postulate that viral diversity observed in these individuals is mostly a result of recombination and to a very limited extent through point mutations. This study confirms that multiple HIV -1 subtypes and recombinant viruses co-circulate in the population of Mbeya, and that there is a high prevalence of dual infections. While dually infected individuals harbour highly divergent viruses with high fluctuation of diversity over time, the diversity at a single timepoint is usually constrained. An investigation of full-length gag and nef suggests that the major mechanism of viral evolution is through recombination.